CORRELATION OF POTENTIAL FACTOR THAT AFFECT THE QUALITY OF LIFE OF OSTEOARTHRITIS PATIENT IN RSUD DR. SOETOMO, SURABAYA BASED ON TRANSLATED AND TRANSADAPTED OF THE KNEE OSTEOARTHRITIS OUTCOME SCORE (KOOS) QUESTIONNAIRE - Ahmad Naqib bin Baharom; Sulis Bayu sentono (Universitas Syiah Kuala, 2018)
Abstract. Background: Osteoarthritis is a degenerative process disease and is a leading cause of pain and disability. It is also ranked as 11th highest contributor to disability worldwide. Many risk factors have been known that can speed the progression of osteoarthritis.Purpose: To study the correlation between age, gender, BMI, physical activities and history of trauma with quality of life in clinically diagnosed osteoarthritis patients in Orthopaedic and Traumatology Outpatient Clinic between January 2015 until December 2016.Method: This research is a hospital-based cross-sectional analytic study. The samples are clinically diagnosed osteoarthritis patients in Orthopaedic and Traumatology Outpatient Clinic in RSUD Dr. Soetomobetween January 2015 until December 2016.Results: There were 43 patients that can be reach in Orthopaedic and Traumatology Outpatient Clinic in RSUD Dr. Soetomo between January 2015 until December 2016. The mean age is 54.35 ± 5.32 years old and the most gender in the subjects are female (72.1%). The mean BMI of the subjects are 26.20 ± 3.75 and most of them are overweight (60.5%). Most of the subjects never have history of trauma (76.7%) and also have an inactive physical activities (65.1%). The quality of life of the research subjects have a mean score of 42.86 ± 12.54. After that, the correlation between the age, gender, BMI, physical activities, history of trauma and quality of life is tested. It is found that there is a significant correlation between gender, BMI and physical activities with quality of life but no significant correlation between age and history of trauma with quality of life.Conclusion: Gender still a main role in osteoarthritis development with women have a higher risk. Also patients with higher BMI and inactive patients will have a decrease quality of life. Most of the patients have an moderate quality of life.Keywords: osteoarthritis, quality of life, age, gender, physical activities, BMI, history of trauma